TINJAUAN MAṢLAHAH MURSALAH ATAS TRADISI KAMAR KOSONG DALAM PERKAWINAN ADAT MELAYU DESA GURUN TUO JAMBI - Ahmad Fayyadh (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2022)
Giving “vacant room money” to women is a hereditary tradition followed by the people of Gurun Tuo village, Jambi Province. Even though it has become a custom for quite a long time, the tradition of empty room fees still raises pros and cons in the local community and surrounding areas. This is reviewed with the theory of maṣlahah mursalah, because maṣlahah mursalah is considered an effective legal scale to answer the problems of Muslims in the contemporary era. This study uses a sociological normative qualitative approach, using primary and secondary data sources. This study describes a series of marriages in the village of Gurun Tuo, including: pioneering (ta'aruf and applications), a collection (thanksgiving) in this series the women determine the nominal amount of the vacant room money, then the gernak-gerning (alms) stage, and the last series is wedding reception. If we look at it from the perspective of maṣlahah mursalah, the current implementation of the vacant room customary money is not in line. Because it does not meet one of the conditions for determining maṣlahah mursalah, namely the benefit must be general, not specific to individuals.